The Influence of Liquid Collateral Types and Credit Processes Through Digital Marketing On Customer Decisions To Take Cash Collateral Credit at Bank ABC - Ika Novita Widyanti (Publikasi Indonesia, 2024)
This study aims to find out about the influence of the type of liquid collateral on the customer's decision to take Cash Collateral Credit and; The influence of the credit process through digital marketing on the customer's decision to take Cash Collateral Credit at Bank Jatim. As mentioned earlier, this research is a qualitative research framed using the CIT (Critical Incident Technique) method. It was found that CCC's outstanding did not grow significantly and was still far below 1% (one prosen) both in terms of total outstanding KYD (Credit Granted) and from total outstanding deposits. The fact that CCC's NoA did not grow significantly and is still further below 1% (one prosen) is both reviewed from the total NoA of KYD given and of the total NoA of deposits. Moreover, from Table 1.2, it can be seen that liquid-type collateral such as CCC at Bank Jatim seems less interested when compared to loans with non-liquid collateral.